1998
DOI: 10.1038/sj.leu.2401205
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF receptor targeted treatment of primary AML in SCID mice using Diphtheria toxin fused to huGM-CSF

Abstract: The severe combined immunodeficient (SCID) mouse model may be used to evaluate new approaches for the treatment of acute myeloid leukemia (AML). We have previously demonstrated the killing of SCID mouse leukemia initiating cells by in vitro incubation with human GM-CSF fused to Diphtheria toxin (DT-huGM-CSF). In this report, we show that in vivo treatment with DT-huGM-CSF eliminates AML growth in SCID mice. Seven cases of AML were studied. SCID mice were treated intraperitoneally with the maximally tolerated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In addition, dose effect titration experiments using the AML/SCID leukemia model indicated that efficient elimination of AML cells was achieved at dose levels as low as 6.25 g/kg/day. 8 However, a comparative evaluation of the systemic toxicity, the bone marrow-specific toxicity and the antileukemic efficacy of DT-mGM-CSF treatment in vivo would enable us to derive a therapeutic ratio. We compared the continuous administration scheme by means of osmotic pumps placed i.p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, dose effect titration experiments using the AML/SCID leukemia model indicated that efficient elimination of AML cells was achieved at dose levels as low as 6.25 g/kg/day. 8 However, a comparative evaluation of the systemic toxicity, the bone marrow-specific toxicity and the antileukemic efficacy of DT-mGM-CSF treatment in vivo would enable us to derive a therapeutic ratio. We compared the continuous administration scheme by means of osmotic pumps placed i.p.…”
Section: Discussionmentioning
confidence: 99%
“…The ADP ribosylation assay showed a comparable dose-dependent activity for DT-huGM-CSF, DTmGM-CSF and DT 388 proteins. 8 Murine GM-CSF was radiolabeled using the method of Bolton and Hunter 29 and the binding characteristics were determined as previous described. 5,30 In vitro cytotoxicity assays 3 H-thymidine ( 3 H-TdR) incorporation assays were performed as described.…”
Section: Growth Factor Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Another concept targeting cell-surface molecules is the use of recombinant GM-CSF/diphtheria toxin or recombinant IL-3/diphtheria toxin fusion proteins [94,96]. In this regard it is noteworthy that leukemic stem cells differ from normal hematopoietic stem cells in aberrant expression of the IL-3 receptor alpha chain (CD123) (Fig.…”
Section: New Drugs Targeting Specific Cell-surface Markers On Aml (Stmentioning
confidence: 99%
“…These chimeric proteins have shown promise in their ability to kill certain tumors by binding the receptors and then initiating cell lysis. [113][114][115][116][117][118][119][120] Although this approach is designed to kill tumors expressing the receptors for a particular cytokine, it could be easily modified to treat autocrine tumors which express a given cytokine as well as the cognate receptor.…”
Section: Therapy Directed At Cytokine Gene Expressionmentioning
confidence: 99%